A cross sectional study to assess knowledge, attitude and practice regarding voluntary blood donation among medical students of Jabalpur, central India - Verma, Prashant; Thakur, Aditya; Saklecha, Deepak; Kasar, Pradeep Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: Blood transfusion is a crucial and an essential part of any nation’s health care delivery system for a lifesaving Interventions. Positive attitude towards blood donation practices among the younger generation would play a crucial role in improving health care structure. Objectives of the study were to assess knowledge, attitude, and practice towards blood donation and its associated factors among undergraduate medical students. Methods: It was a descriptive cross sectional study conducted on the 322 under graduate medical students of different professional years during September to December 2016 at Netaji Subash Chandra Bose medical college Jabalpur (M.P.). A pretested, self administered, structured questionnaire was used to collect data on knowledge, attitude and practice regarding voluntary blood donation. Scores for three domains i.e. knowledge, attitude, practice was calculated. Data on Socio demographic details and reason behind non donation of blood were also collected. Results: On correlation between the scores of attitude and practice with knowledge. Attitude has a positive statistically significant correlation with the increase in knowledge and vice versa. On the other hand Increase in attitude shows a negative statistically significant correlation with practice and vice versa. Students belongs to >20 years of age group has significantly more knowledge and good attitude regarding blood donation (p<0.001). Female students when compared with male have more knowledge and good attitude regarding blood donation. But in case of practice of blood donation female significantly lag behind male students (p<0.001). Conclusions: Opportunities for blood donations should be created regularly by conducting blood donation camps this will not only increase the Sense of social responsibility among medical students through positive attitude but will also narrowed down the gap between the demand and the supply of the country.